Landscaping biostatistics education in India - Singh, Ranjana; Zodpey, SanjayP; Sharma, Kavya; Bangdiwala, ShrikantI; Ughade, Suresh (Indian journal of public health, 2012)
Biostatistics plays an important role in measuring, understanding, and describing the overall health and well-being of a population. Biostatistics as a subject evolved from the application of statistics in various research aspects of biology, biomedical care, and public health. However, with a recent increase in number of health and pharmacy related research, the demand for trained biostatisticians is also increasing. The present paper is an attempt to undertake a situational analysis of biostatistics education in India. A systematic, predefined approach, with three parallel strategies was used to collect and assemble the data regarding training in biostatistics in India. Our study results show that there is paucity of programs providing specialized training in biostatistics in India. Only about 19 institutions in India are offering various courses in biostatistics/medical statistics/health statistics/biometry. It is important to look into the current capacity building initiatives in this domain. Some other means for giving importance to biostatistics could be by making it a separate branch/specialization in a majority of the institutions, particularly in medical colleges.